Systemic Immune-Inflammation Index and Systemic Inflammation Response Index Predict the Response to Radioiodine Therapy for Differentiated Thyroid Cancer [Corrigendum] - Wang Y; Chang J; Hu B; Yang S (Journal of Inflammation Research)
Wang Y, Chang J, Hu B, Yang S. J Inflamm Res. 2024;17:8531—8541. The authors have advised the affiliation list on page 8531 is incorrect. The correct author list and affiliations are as follows. Yan Wang1,2, Junshun Chang2, Ben Hu3, Suyun Yang2 1Academy of Medical Sciences, Shanxi Medical University, Taiyuan, Shanxi, 030001, People’s Republic of China 2Department of Nuclear Medicine, First Hospital of Shanxi Medical University, Taiyuan, Shanxi, 030001, People’s Republic of China 3The Fifth Clinical Medical School of Anhui Medical University, Hefei, Anhui, People’s Republic of China The authors apologize for this error.